TIGER PARENTING’S POWER DOMINANCE IN “TWO KINDS” SHORT STORY: A CRITICAL DISCOURSE ANALYSIS - Windianto, Cahya Pratama (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2022)
This study aims to examine the short story entitled “Two Kinds”. The method used in this study is descriptive qualitative. In gathering the data, the writers applied close reading to determine the sentences which show the social wrong. In analyzing the data, the writers applied transitivity as the tool to analyze the sentences. After analyzing the data, the writers interpreted and related the sentences with social theories, which are tiger parenting and second generation Asian American. The results of this study show that the main character’s mother applied abusive methods as discussed in the tiger parenting explanation. The transitivity is used to prove that the parent, specifically the mother in the story, applies tiger parenting’s abusive system. The abusive system of the mother is realized through physical actions, mental affection, and verbal utterances to her daughter. The short story also contains the second generation of Asian American phenomena. As the second generation of Asian American, the main character rebels against the tiger parenting shown by her utterances towards her mother.